Features of syntactic derivation in the military vocabulary of Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
This article provides a comprehensive study of formal syntactic structures in the names of modern weapon, accoutrements and military installations. The main trends and characteristics of syntactic derivation in the military vocabulary of Ukrainian language were analyzed.
Keywords: military vocabulary; terminological word group; syntactic derivation